Spatially explicit approaches to build food, biodiversity, and climate positive futures - Mittra, Sarika; Frank, Federico; Jones, Sarah (CGIAR, 2024)
Achieving food, biodiversity, and climate goals in tandem requires managing land-use systems for multiple purposes. This NEXUS Gains Talk focuses on using spatial datasets to guide and prioritize interventions on and off-farm to support food security, biodiversity conservation, and climate mitigation objectives.